ANALISIS PENERAPAN STANDARD PRECAUTIONS DALAM PENCEGAHAN DAN PENGENDALIAN HAIs (HEALTHCARE ASSOCIATED INFECTIONS) DI RSUD RAA SOEWONDO PATI - Astri Budhi Satiti; Putri Asmita Wigati; Eka Yunila Fatmasari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
The incidence of Health Care Associated Infections (HAIs) is Surgical Site Infection (SSI) in RAA Soewondo Hospitals, Pati Regency on September 2015 is 3,09%, October 2015 is 3,44%, and December 2015 is 7,79%. Therefore, it is very important to apply Standard Precautions facilities because it proved to prevent transmission of infections associated with health care. This research is qualitative descriptive research aimed to analyze the application of standard precautions in the prevention and HAIs (Healthcare Associated Infections) control at RAA Soewondo Hospitals, Pati Regency. Data were collected by in-depth interview and observation non participatory method. The key informants of this research are IPCN. The triangulation informants are IPCLN and head of nursing units. The research results show that the standard precautions been socialized and applied in RAA Soewondo Hospitals, Pati Regency, but the level of several compliance still below standard. In planning, there are still undetermined performance indicators of components standard precautions. In organizing, there has been no a division of individual duties for all of the PPI committee members and still have constraints. There are barriers or obstacles in implementation, such as human behavior less adherent and less infrastructure. Monitoring and evaluation of standard precautions that the schedule only carried out when the audit is every quarter in a year and some components of standard precautions have not been audited. Suggestions in this research are to make more detailed regulations, according to the situation of the hospital; determine the distribution of individual duties to all members of the PPI committee in detail; improve monitoring or audit; make the system of reward, and increase the inadequate facilities.